Manajemen Pondok Pesantren Annuqayah Dalam Mengembangkan Sdm Santri Dibidang Entrepreneurship - Nur Isnaini (MABIS: Jurnal Manajemen Bisnis Syariah, 2022)
Pesantren is a very appropriate institution or forum to instill the spirit of entrepreneurship with Islamic nuances, namely teaching through verses of the Quran that explain how to become Islamic entrepreneurs, so that the knowledge of the world and the afterlife of the students becomes balanced. The motto used in this study is descriptive qualitative research, which will convey descriptions of the management of the development of student human resources in the field of entrepreneurship. The purpose of this study is to find out how the role, programs, and methods of Islamic boarding schools in managing and preparing students in the field of entrepreneurship. Researchers make Annuqayah Islamic boarding school the object of research because the Islamic boarding school already has a variety of business units which include, Annuqayah mini-market, UJKS, restaurants, bottled drinking water kopontren, ABC (Annuqayah business center), DCA photocopy, P2KA consumption service center, salt field. To follow up on this research, it is necessary for the Annuqayah Islamic Boarding School to further optimize management in developing student human resources in the field of entrepreneurship.